2022
DOI: 10.3389/fimmu.2022.989263
|View full text |Cite
|
Sign up to set email alerts
|

NRF2-directed PRPS1 upregulation to promote the progression and metastasis of melanoma

Abstract: Phosphoribosyl pyrophosphate synthetase 1 (PRPS1) is the first enzyme in the de novo purine nucleotide synthesis pathway and is essential for cell development. However, the effect of PRPS1 on melanoma proliferation and metastasis remains unclear. This study aimed to investigate the regulatory mechanism of PRPS1 in the malignant progression of melanoma. Here, we found PRPS1 was upregulated in melanoma and melanoma cells. In addition, our data indicated that PRPS1 could promote the proliferation and migration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…It has been found that PRPS1 and PRPS2 play important regulatory roles in different malignant tumors. PRPS1 is overexpressed in melanoma and accelerates tumor progression by promoting cell growth, metastasis, and suppressing cell apoptosis 8 . PRPS2 is the target of myeloid proliferative oncogene (c‐Myc), which changes with c‐Myc expression 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that PRPS1 and PRPS2 play important regulatory roles in different malignant tumors. PRPS1 is overexpressed in melanoma and accelerates tumor progression by promoting cell growth, metastasis, and suppressing cell apoptosis 8 . PRPS2 is the target of myeloid proliferative oncogene (c‐Myc), which changes with c‐Myc expression 9 .…”
Section: Introductionmentioning
confidence: 99%
“…PRPS1 is overexpressed in melanoma and accelerates tumor progression by promoting cell growth, metastasis, and suppressing cell apoptosis. 8 PRPS2 is the target of myeloid proliferative oncogene (c‐Myc), which changes with c‐Myc expression. 9 Previously, the expression levels of PRPS2 vary in different tumor tissues, and its related mechanism is preliminarily discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies primarily focused on decoding melanoma metastasis from a single molecule or single pathway perspective [ 10 12 ]. However, the tumor microenvironment (TME) of melanoma is complex and dynamic, with intricate crosstalk between cells, resulting in significant losses of key metastasis-related information.…”
Section: Introductionmentioning
confidence: 99%